Enhancing Firm Value through Green Accounting and Environmental Performance: The Mediating Effect of Profitability - Sayu Made Anggreni; Eka Ardhani Sisdiyani; I Dewa Nyoman Badera (Jurnal Dinamika Akuntansi, 2025)
Purposes: With profitability acting as the mediating variable, the study’s objective is to evaluate the impact of implementing green accounting and its environmental implications on firm value in manufacturing companies listed on the Indonesia Stock Exchange between 2020 and 2022. Methods: The approach used in this study is a quantitative approach. The research sample was 171 cases. Data analysis was performed using path analysis using Eviews 10, and the Sobel test was used to conduct the mediation test. Findings: This study indicates that green accounting and environmental performance impact can enhance firms’ value. Employing green accounting practices and improving environmental performance impact enhances profitability. The greater the profit, the higher the firm’s value. Profitability may play a role in determining the effect of green accounting and environmental performance impact on firm value. Novelty: This research supports the idea that profitability can be a mediator in understanding the effect of green accounting and environmental performance impact on the firm value of Indonesian industries listed on stock exchanges. Profitability as a mediating variable requires further investigation, as green accounting practices and improved environmental performance impact can increase operational efficiency, reduce costs, and ultimately improve a business’s profitability. Increased profit makes a company more valuable to investors and other stakeholders.